Barrel Cortical Neuron Integrates Triple Associated Signals for Their Memory Through Receiving Epigenetic-Mediated New Synapse Innervations. (7th November 2017) - Feng, Jing; Lu, Wei; Wang, Dangui; Ma, Ke; Song, Zhenhua; Chen, Na; Sun, Yan; Du, Kaixin; Shen, Mengmeng; Cui, Shan; Wang, Jin-Hui
Abstract: Associative learning is common way for information acquisition. Associative memory is essential to logical reasoning and associative thinking. The storages of multiple associated signals in individual neurons facilitate their integration, expand memory volume, and strengthen cognition ability. Associative memory cells that encode multiple signals have been reported, however, the mechanisms underlying their recruitment and working principle remain to be addressed. We have examined the recruitment of associative memory cells that integrate and store triple sensory signals as well as the potential mechanism of their recruitment. Paired mouse whisker, olfaction, and tail stimulations lead to odorant-induced motion and tail-induced whisker motion. In mice of expressing this cross-modal response, their barrel cortical neurons become to encode odor and tail signals alongside whisker signal. These barrel cortical neurons receive new synapse innervations from piriform and S1-tail cortical neurons. The emergence of cross-modal responses as well as the recruitments of new synapse innervations and associative memory cells in the barrel cortex need miRNA-324 and miRNA-133a, which downregulate Ttbk1 and Tet3. The co-activations of sensory cortices recruit their mutual synapse innervations and associative memory cells that integrate and store multiple associated signals through epigenetic-mediated process.